Signs of postmodernist style and poetic skill in the poems of Serik Aksunkaruly - Omarova G. T., Al'bekova A. S., Kukenova G. A. (The development of modern education in the context of educational competence, 2025)
this paper explores the postmodern features in the poetry of Serik Aksunkaruly, one of the most spiritual figures in modern Kazakh literature. It examines how his work blends deep national symbolism, historical and cultural allusions, and elements such as fragmentariness, reminiscence, and pluralism. Through poems like "Hey, Baibori, Baibori", "Mozart and Salieri (Modern Version)", and "Homo Soveticus", the paper analyzes how Aksunkaruly expresses resistance, identity, and artistic integrity. His poetic style, rooted in classical tradition yet shaped by postmodernist methods, reveals a strong civic stance and spiritual depth, making him a significant representative of postmodern Kazakh poetry.
Keywords: постмодернизм; духовность; spirituality; национальная идентичность; postmodernism; плюрализм; pluralism; national identity; фрагментарность; аллюзия; реминисценция; reminiscence; казахская поэзия; литературный символизм; Kazakh poetry; fragmentariness; allusion; literary symbolism